Construction of Plasmonic Nano‐Biosensor‐Based Devices for Point‐of‐Care Testing. Issue 11 (24th October 2017) - Wang, Yangyang; Zhou, Jianhua; Li, Jinghong
Abstract: Next‐generation healthcare equipment and devices are in great demand for point‐of‐care testing (POCT), in view of their applications in rapid disease diagnosis, personalized medicine, portable or mobile health care, nontechnician assays, etc. Localized surface plasmon resonance (LSPR) biosensors, which are based on noble‐metal nanostructures and which provide fast, real‐time, nonlabeled, and sensitive biochemical detections, have become one of the leading candidates for POCT. The advances in nanofabrication, molecular biotechnology, and optoelectronics integration technology have promoted LSPR biosensing to low‐cost, easy‐to‐use, and on‐site POCT. Here, a synopsis of LSPR nano‐biosensors and LSPR‐based POCT devices is provided by delineating the fundamental principles of LSPR sensing, various metal nanostructures, the modification layers on LSPR nanostructures, and the integration of LSPR biosensors into devices. Examples of applications of existing LSPR‐based microfluidic platforms and POCT devices in healthcare, public security, environmental monitoring, and food safety, for example, are given. Finally, the challenges and perspectives of developing LSPR‐based POCT techniques are highlighted. A relatively complete and instructive summary is provided for the development of plasmonic nano‐biosensor‐based portable, mobile, and wearable POCT devices. Abstract : The construction of plasmonic nano‐biosensor‐based point‐of‐care testing (POCT) devices is summarized by considering four core issues: the plasmonic nanosubstrates, the detection strategies, the integration of plasmonic nano‐biosensors into microfluidic chips, and the building of POCT devices. Advances in plasmonic nano‐biosensor‐based POCT devices are promising to benefit public healthcare, rapid diagnosis, environmental monitoring, and so on.